Link of volcanic activity and climate change in Altai studied in the ice core from Belukha Mountain - N. S. Malygina; T. V. Barlyaeva; T. S. Papina (Лëд и снег)
In the present research we discuss a role of volcanic activity in Altai thermal regime. Here we analyses the sulfate and temperature data reconstructed from the natural paleoarchive – ice core from the Belukha Mountain saddle. Sulfate ice-core reconstructions can serve as volcanic markers. The both – sulfate and temperature reconstructions – are for the last 750 years. As the characteristic of volcanic activity we consider Volcanic Explosivity Index (VEI), Dust Veil Index (DVI) and Ice core volcanic index (IVI). The analysis was done using wavelet analysis and analysis of wavelet cross coherence and phase. As the result, we conclude that observed increases in the values of the indexes VEI, DVI, IVI basically correspond to decreases of temperature and increases of sulfate concentrations. This confirms the dependence of changes in the thermal regime of the Altai from volcanic activity. But in the 1750–1850 years period there is a delay of the changes in temperature with respect to the changes in volcanic activity. We suggest that it can be due to the superposition of the influence of solar and volcanic activity on changes in the thermal regime of Altai.